PERAN DANA PIHAK KETIGA DALAM MEMEDIASI PENGARUH NET INTEREST MARGIN TERHADAP PERTUMBUHAN KREDIT PADA PERBANKAN YANG GO PUBLIC DI BURSA EFEK INDONESIA - Pristin Prima Sari; Ardian Prima Putra (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2020)
AbstractsThe study found empirical proof the role of third party funds (DPK) mediate the influence of net interest margin (NIM) on bank credit growth listed in Indonesia Stock Exchange on 2015-2018. The study uses data from the bank’s annual financial statements. The Study covers 22 commercial banks resulting in 88 bank-year observations. Research using Smartpls 3.0 statistical tools to process data and path analysis to compute data. The results obtained are third party funds (DPK) that can positively mediate the influence of net interest margin (NIM) on credit growth. The greater DPK create the profitability of bank interest rates increases bank credit growth. Partially Net interest margin (NIM) and third party funds (DPK) can increase bank credit growth. Net interest margin (NIM) also can increase the amount of third party funds (DPK). This study is useful for bank management to make decisions on determining bank margins, obtaining third party funds (DPK) and credit, for the government for study and mapping materials related to bank lending and the amount of bank interest rates, for further research is for reference material related to factors affecting lending.Keywords : Net Interest Margin, Third Party Fund, Credit, IDX